HUBUNGAN ANTARA ATTACHMENT IBU DAN SELF-ESTEEM PADA MAHASISWA TINGKAT AKHIR - Karelina Primavitri; Agustina Agustina; Hanna Christina Uranus (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aimed to examine the relationship between maternal attachment and self-esteem among final-year university students in Indonesia. Final-year students are in a phase that is vulnerable to academic pressure, thesis completion demands, and career uncertainty, all of which may affect self-evaluation. However, studies that specifically examine the relationship between maternal attachment and self-esteem among final-year students within the Indonesian cultural context remain limited. This study involved 319 final-year university students. Self-esteem was measured using the Rosenberg Self-Esteem Scale (RSES), while maternal attachment was assessed using the Inventory of Parent and Peer Attachment (IPPA). Data were analyzed using Pearson’s correlation after the assumptions of normality and linearity were met. The results showed a significant positive relationship between maternal attachment and self-esteem (r = 0.837, p < 0.001), indicating that the higher the quality of maternal attachment, the higher the students’ self-esteem. These findings contribute scientifically by extending empirical evidence on the role of the mother–child relationship in shaping self-esteem among final-year university students, particularly within the Indonesian cultural context, where mothers are often regarded as an important source of emotional support during the transition to early adulthood. ABSTRAK Penelitian ini bertujuan untuk menguji hubungan antara attachment ibu dan self-esteem pada mahasiswa tingkat akhir di Indonesia. Mahasiswa tingkat akhir berada pada fase yang rentan terhadap tekanan akademik, tuntutan penyelesaian tugas akhir, serta ketidakpastian karier yang dapat memengaruhi evaluasi diri. Namun, penelitian yang secara khusus menelaah hubungan attachment ibu dan self-esteem pada mahasiswa tingkat akhir dalam konteks budaya Indonesia masih terbatas. Penelitian ini melibatkan 319 mahasiswa tingkat akhir. Self-esteem diukur menggunakan Rosenberg Self-Esteem Scale (RSES), sedangkan attachment ibu diukur menggunakan Inventory of Parent and Peer Attachment (IPPA). Data dianalisis menggunakan korelasi Pearson setelah asumsi normalitas dan linearitas terpenuhi. Hasil analisis menunjukkan adanya hubungan positif yang signifikan antara attachment ibu dan self-esteem (r = 0.837, p < 0.001), yang mengindikasikan bahwa semakin tinggi kualitas attachment ibu, semakin tinggi pula self-esteem mahasiswa. Temuan ini memberikan kontribusi ilmiah dengan memperluas bukti empiris mengenai peran relasi ibu–anak dalam pembentukan self-esteem pada populasi mahasiswa tingkat akhir, khususnya dalam konteks budaya Indonesia yang menempatkan ibu sebagai sumber dukungan emosional yang penting pada masa transisi menuju dewasa awal.